Main entrance of the Suswani Mata Temple - Temples of India Project Team (Jio Institute, 2024)
Seen here is the main entrance of the Suswani Mata Temple which was made from the donation given by Shri Punamchandaji Surana, son of Dhanpatsinha. This mandapa (pillared hall) has been restored several times, the latest one being carried out in the last decade. A plaque providing information of the doner is visible above the main entrance.